31. HEALTH CARE NEEDS OF FIRST-YEAR STUDENTS AT VIETNAM NATIONAL UNIVERSITY ENROLLING IN 2021 - 2022 (Vietnam Journal of Community Medicine, 2025)
Objective: Identifying the health care needs of first-year students at Vietnam National University, Hanoi (VNU), academic year 2021-2022.Subject and method: Cross-sectional descriptive study on 1,829 first-year students of Vietnam National University, Hanoi admitted and had an entrance health check at VNU Hospital.Results: 73.81% of students have a need to use health consulting services. The content that students want to be consulted the most is psychological counseling, mental health (72.59%), nutritional counseling (64.89%), and accident and injury counseling is 52.59%. 50.89% of students want to set up a counseling facility at their school and 47.19% of students want to set up a counseling facility at VNU Hospital. The need for training in first aid accounts for 65.12%. The main first aid content that students want to be trained in is: first aid for cardiac arrest 64.07%; first aid for fainting 58.86%; first aid for skin lacerations 55.33%; first aid for fractures 44.92%. Students mainly choose the training method 63.39%; regular teaching 30.39%..Conclusion: The need for health care and first aid consultation among students is very large and they want to be consulted right at their school as well as at VNU Hospital.
Keywords: students; health care needs; health advice